Bacteriophage-Mediated Control of Biofilm: A Promising New Dawn for the Future - Chang, Cheng; Yu, Xinbo; Guo, Wennan; Guo, Chaoyi; Guo, Xiaokui; Li, Qingtian; Zhu, Yongzhang (Frontiers in Microbiology, 2022)
Biofilms are complex microbial microcolonies consisting of planktonic and dormant bacteria bound to a surface. The bacterial cells within the biofilm are embedded within the EPS (extracellular polymeric substance) matrix consisting mainly of exopolysaccharides, secreted proteins, lipids, and extracellular DNA. This structural matrix poses a major challenge against common treatment options due to its increased and extensive antibiotic-resistant properties. Because biofilms are so recalcitrant to antibiotics, they pose a unique challenge to patients in a nosocomial setting, mainly linked to lower respiratory, urinary tract, and surgical wound infections as well as the medical devices used during treatment and post-treatment checkups. Another unique property of biofilm is its ability to adhere to both biological and man-made surfaces, allowing growth on human tissues and organs, hospital tools, and medical devices, etc. Based on prior understanding of bacteriophage structure, mechanisms, and its effects on bacteria eradication, leading research has been conducted on the effects of phages and its individual proteins on biofilm and its role in overall biofilm removal while also revealing the obstacles this form of treatment currently have. The expansion in the phage host-species range is one that urges for improvement and is the focus for future studies. This review aims to demonstrate the advantages and challenges of bacteriophage and its components on biofilm removal, as well as potential usage of phage cocktail, combination therapy, and genetically modified phages in a clinical setting.